Pengaruh Harga Terhadap Keputusan Pembelian Paket Data Internet Telkomsel (Studi Kasus: Mahasiswa Prodi Manajemen, Fakultas Ekonomi Dan Bisnis Islam, Universitas Islam Negeri Sumatera Utara, Medan) - Ayu Widyastuti R; Halimah Safitry A; Malkan Yahya A; Nurhafifah Saragih; M. Taufiq Azhari (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to determine the effect of the price of Telkomsel internet data packages on consumer purchasing decisions partially. The research method used is a quantitative research method with causal associative research. The data collection method used in this research is by means of observation, field research, and documentation studies with the number of respondents (N) = 20. The data from this study were processed using validity test, reliability test, and simple linear regression analysis. The results of the validity and reliability tests show that all the instruments used by each variable can be said to be valid and reliable. The results of the t-test on the Price (X) variable are 12.865 which is greater than the t-table of 1.725 (t-Hitung > t-Tabel) and a significance value of 0.000 which is smaller than 0.05. So it can be concluded that H0 is rejected and Ha is accepted. The results of this hypothesis test show that partially there is a positive and significant effect of the Price variable on the Purchase Decision variable (Y).